EFFICACY ANALYSIS OF REGIONAL ANALGESIA IN EARLY POSTTRAUMATIC PERIOD - V. A. Panov; R. E. Lakhin; A. V. Schegolev (Вестник анестезиологии и реаниматологии, 2017)
A prospective randomized study was conducted in order to evaluate the quality of anesthesia for patients with hip fracture when using various methods of regional analgesia. It has been proved that continuous administration of local anesthetic to the femoral nerve is the most efficient one among the peripheral regional methods of pain syndrome management by hip shaft fracture.